Mitigating soil water deficit using organic waste compost and commercial water retainer: a comparative study under semiarid conditions - Hatem Zgallai (17792567) (2023)
Semiarid regions have particularly been confronted with climate change effects reflected by the consistent decrease of rainfall and increase of evapotranspiration. This drought stress constitutes the main constraint for agricultural production improvement, which is aggravated by the fact that strategic (field) crops are mostly grown under rainfed systems. Therefore, the objective of this field study was to improve soil water retention by the application of two conditioners namely, an organic waste compost (DS) and a synthetic water-retaining hydrogel (WS). These amendments were applied to an agricultural soil for the cultivation of fodder maize under normal and deficit irrigation regimes. Advanced analysis showed a general disruption of plant growth parameters under water stress. However, both amendments attenuated this negative effect with respect to control by improving soil water status. More precisely, the measured soil water tension at the start of the dry season was the lowest in presence of DS (48 centibars), followed by WS (61 centibars), then unamended soil (83 centibars). Besides, compost application resulted in higher moisture (13.3%), nitrogen (0.36%), and organic matter (0.56%) in soil than the synthetic hydrogel at the end of the field experiment. Soil and plant characterization highlighted the combined effect of water deficit and conditioner type. Indeed, the consistent increase of soil water content in the presence of DS and WS improved all the addressed plant parameters when compared with untreated soil. Infrared thermal imaging showed that canopy temperature was lower in presence of both amendments while dry biomass yield increased by 38% when water supply was limited. Nevertheless, the long-term sustainability of the soil system appears to be better maintained in the presence of the organic waste compost. The latter has the added advantage of improving soil fertility in contrast to inert polymers. Other Information Published in: Euro-Mediterranean Journal for Environmental Integration License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s41207-023-00437-4